Wound Healing Potential/Activity of Polyherbal Ointment Containing Salvadora persica, Azadirachta indica and Calendula officinalis Extracts: An Experimental Study: Wound Healing Potential: An Experimental Study - Imran, Hina; Rehman, Atiq-ur-; Sohail, Tehmina; Shaukat, Sohail; Khokar, Ayesha (Biological Sciences - PJSIR, 2022)
The present study explore the wound healing potential of a novel herbal ointment formulation, fast wound healing ointment (FWHO) composed of 10% w/w crude ethanolic extracts of Salvadora persica (sticks), Azadirachta indica (leaves) and Calendula officinalis (whole plant) on excision wound model in albino rats. The FWHO was applied topically once daily on the wound to evaluate the rate of contraction and period of epithelialization in rats. Complete contraction and epithelialization of wound was observed at 19 day (P<0.0005) in test group animals compared with standard (polyfax skin ointment) at 23 day (P<0.0005) and control group (blank petroleum jelly) at 29 day respectively. It was observed that 10% FWHO has potent wound healing capability as evidenced by decrease in the period of epithelialization and increase in the rate of wound contraction in test group as compared to the standard and control groups. The test group illustrates 34.4%, while the standard group shows 20.6% decrease in the time of epithelialization as compare to control group. The study revealed that test ointment (10% FWHO) has a potential to promote wound healing by accelerating the rate of epithelialization and scar formation as compare to standard (polyfax skin ointment) and control (blank petroleum jelly) groups.